Optimization of Certain Parameters for Transformation of indica Rice Hom Kra Dang Ngah Variety via Agrobacterium-Mediated Transformation - Yinxia, Zhang; Te-chato, Sompong (Agriculture and Natural Resources, 2015)
A transformation experiment was carried out by optimizing three important parameters: the age of calli, infection time and the optimum density of Agrobacterium suspension. A high efficiency Agrobacterium-mediated transformation system was established for the indica rice Hom Kra Dang Ngah variety. Embryogenic calli with high regeneration capability were incubated under different conditions with Agrobacterium tumefaciens strain EHA105 harboring plasmid pCAMBIA1304-EPSPs. The plasmid contains the enzyme gene 5-Enolpyruvylshikimate 3-phosphate synthase (epsps) as a selection marker gene and β-glucuronidase (gus) as a reporter gene. After 2 wk of Agrobacterium elimination and 4 wk of culturing on a selection medium containing 0.5 mM glyphosate (subcultured at 2-weekly intervals) the results showed that the six-week-old calli infected with bacterial suspension at OD600 0.6 for 20 min gave the highest frequency of gus gene expression of 83.5%. The target gene was confirmed using polymerase chain reaction.